Frequency of Infection in Open Fracture Shaft of Femur Treated by Reamed versus Unreamed Interlocking Nails (Medical Forum Monthly, 2024)
Objective: To compare the frequency of infection in open fracture shaft of femur treated by reamed versus unreamed interlocking nails.Study Design: Randomized control trial study.Place and Duration of Study: This study was conducted at the department of Orthopaedics unit, Nishtar Hospital Multan from December 2016 to May 2017.Materials and Methods: All the data was entered and analyzed using computer program SPSS version 21. Descriptive statistics were used to calculate mean and standard deviation for age and duration of fracture. Frequencies and percentages were calculated for gender, blood culture, open fracture and infection. Chi-square test was applied to test the hypothesis. Confounders and Effect Modifiers like age and gender were controlled by stratification of data. Post stratification chi square test was applied. P value <0.05 was considered significant.Results: A total of 484 patients selected for this study and divided into two equal groups 242 in each group. That infection was detected in 5.4% patients (Table-2).When we correlate outcome variable (Infection) with groups, in group A, in 5 (2%) patients observed with infection and in 237 (98%) was not found infection, similarly when we correlate it in group B, 21 (8.6%) patients have infection and in 221 (91.4%) infection was not found. P value was 0.001 a significant value.Conclusion: our results revealed that management of femoral shaft fracture with reamed intramedullary nail is better than undreamed intramedullary nailing because it aids fracture healing and have less infection rate.